2017
DOI: 10.1080/14767058.2017.1293037
|View full text |Cite
|
Sign up to set email alerts
|

Sequential use of Foley catheter with misoprostol for second trimester pregnancy termination in women with and without caesarean scars: a prospective cohort study

Abstract: Sequential use of misoprostol and Foley catheter is safe and effective in second trimester pregnancy termination for patients with and without CS scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was reported that Foley catheter procedure in addition to misoprostol was efficient and safe in cases which underwent cesarean. [24] In our studies, 100 cases had cesarean section history. We did not find any significant difference between scarred and unscarred uterines in terms of termination durations.…”
Section: Discussionmentioning
confidence: 60%
“…It was reported that Foley catheter procedure in addition to misoprostol was efficient and safe in cases which underwent cesarean. [24] In our studies, 100 cases had cesarean section history. We did not find any significant difference between scarred and unscarred uterines in terms of termination durations.…”
Section: Discussionmentioning
confidence: 60%
“…However the 6 hour expulsion rate (36.4% versus 0%, p=0.001) and 12 hour expulsion rate (56.36% versus 3.6%, p=0.001) were significantly higher in the mifepristone -misoprostol group. 16 Not even a single women expelled within 6 hours in the mifepristone foley EAS group whereas 20 out of the 55 expelled within this time period in the mifepristonemisoprostol group. Similarly 31 women out of the 55 in the mifepristone-misoprostol group expelled within 12 hours whereas only 2 women out of the 55 in the second group expelled within this period.…”
Section: Figmentioning
confidence: 98%